2010
DOI: 10.1111/j.1365-2435.2010.01711.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the skin‐swelling response to phytohaemagglutinin

Abstract: Summary1. The phytohaemagglutinin (PHA) skin-swelling test is widely used in immunoecology and ecotoxicology to estimate cell-mediated immunity. Although often presumed, the involvement of T cells in generating an immune response to PHA in vivo remains unclear. 2. To investigate the mechanism triggering this response we have compared in zebra finch (Taeniopygia guttata) the immune responses to two PHA isolectins differing in their biological properties and one control protein.3. In Experiment I, we applied PHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
148
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(162 citation statements)
references
References 33 publications
1
148
1
Order By: Relevance
“…These constitutive antimicrobial agents in plasma include lysozymes, nitric oxide, antimicrobial peptides, complement proteins and natural antibodies (Forsman et al, 2010). It is important to note that both the cutaneous immune response, induced by injection of PHA, and bactericidal activity involve components of both the innate and adaptive axes of the immune system (Juul-Madsen et al, 2008;Forsman et al, 2010;Vinckler et al, 2010); additionally, components of the bactericidal response, such as complement proteins, are themselves quite complicated and have multiple functions in vertebrates (e.g. Ricklin et al, 2010).…”
Section: Differences In Immune Responsementioning
confidence: 99%
“…These constitutive antimicrobial agents in plasma include lysozymes, nitric oxide, antimicrobial peptides, complement proteins and natural antibodies (Forsman et al, 2010). It is important to note that both the cutaneous immune response, induced by injection of PHA, and bactericidal activity involve components of both the innate and adaptive axes of the immune system (Juul-Madsen et al, 2008;Forsman et al, 2010;Vinckler et al, 2010); additionally, components of the bactericidal response, such as complement proteins, are themselves quite complicated and have multiple functions in vertebrates (e.g. Ricklin et al, 2010).…”
Section: Differences In Immune Responsementioning
confidence: 99%
“…during step 2). This test assays the proinflammatory response to a foreign plant protein (PHA), which is mainly linked to the accumulation of small lymphocytes and the infiltration of macrophages (Smits et al, 1999;Vinkler et al, 2010). To conduct the PHA test, we measured the right wing web of each bird three times with a digital micrometer (±0.02 mm; Mitutoyo, Japan) to obtain an average pre-swelling measurement and then injected this area with 100 μg of PHA-P (SigmaAldrich, St Louis, MO, USA) diluted in 20 μl of phosphate-buffered saline.…”
Section: Immune Parametersmentioning
confidence: 99%
“…These common results in males could be interpreted on the light of common components in the innate and adaptive axes of the immune system (Forsman et al 2010;Vinkler et al 2010). In fact, some studies have shown that the PHA swelling response is an integration of both specific and induced immunity and also of constitutive and nonspecific immunity (Martin et al 2006a;Salaberria et al 2013).…”
Section: Discussionmentioning
confidence: 99%